Murine endometrial-derived mesenchymal stem cells suppress experimental autoimmune encephalomyelitis depending on indoleamine-2,3-dioxygenase expression - Polonio, Carolina Manganeli; de Freitas, Carla Longo; de Oliveira, Marília Garcia; Rossato, Cristiano; Brandão, Wesley Nogueira; Zanluqui, Nágela Ghabdan; de Oliveira, Lilian Gomes; Nishiyama Mimura, Luiza Ayumi [UNESP]; Barros Silva, Maysa Braga; Garcia Calich, Vera Lúcia; Nisenbaum, Marcelo Gil; Halpern, Silvio; et al. (Portland Press, 2021)
Cellular therapy with mesenchymal stem cells (MSCs) is a huge challenge for scientists, as little translational relevance has been achieved. However, many studies using MSCs have proved their suppressive and regenerative capacity. Thus, there is still a need for a better understanding of MSCs biology and the establishment of newer protocols, or to test unexplored tissue sources. Here, we demonstrate that murine endometrial-derived MSCs (meMSCs) suppress Experimental Autoimmune Encephalomyelitis (EAE). MSC-treated animals had milder disease, with a significant reduction in Th1 and Th17 lymphocytes in the lymph nodes and in the central nervous system (CNS). This was associated with increased Il27 and Cyp1a1 expression, and presence of IL-10-secreting T CD4+ cells. At EAE peak, animals had reduced CNS infiltrating cells, histopathology and demyelination. qPCR analysis evidenced the down-regulation of several pro-inflammatory genes and up-regulation of indoleamine-2,3-dioxygenase (IDO). Consistently, co-culturing of WT and IDO-/- meMSCs with T CD4+ cells evidenced the necessity of IDO on the suppression of encephalitogenic lymphocytes, and IDO-/- meMSCs were not able to suppress EAE. In addition, WT meMSCs stimulated with IL-17A and IFN-γ increased IDO expression and secretion of kynurenines in vitro, indicating a negative feedback loop. Pathogenic cytokines were increased when CD4+ T cells from AhR-/- mice were co-cultured with WT meMSC. In summary, our research evidences the suppressive activity of the unexplored meMSCs population, and shows the mechanism depends on IDO-kynurenines-Aryl hydrocarbon receptor (AhR) axis. To our knowledge this is the first report evidencing that the therapeutic potential of meMSCs relying on IDO expression.